2010
DOI: 10.1080/08856251003658710
|View full text |Cite
|
Sign up to set email alerts
|

Questions of inclusion in Scotland and Europe

Abstract: This paper examines inclusion in Scotland and in Europe. It considers some of the uncertainties surrounding inclusion and the questions which are currently being raised by researchers, teachers and their representative unions, parents and children, many of which give cause for concern. The shifting political and policy contexts and recent patterns and trends in Scotland and across Europe, which illustrate key points of exclusion, as well as some of the challenges to these, are reported. A 'landmark' challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 17 publications
0
21
0
5
Order By: Relevance
“…This growth in knowledge of children's mathematical thinking supported the participating teachers to develop more inclusive pedagogical approaches to mathematics teaching. The important relationship between learning in meaningful contexts and the development of more equitable classrooms is consistent with international policies and practices promoting inclusive education (Thomas, 2013;Slee, 2013;Allan, 2010;Armstrong, Armstrong & Spandagou, 2010). Similarly in elementary mathematics classrooms in which lessons are structured to include all children purposefully, there are clear connections between teaching content, teachers' pedagogical knowledge and knowledge of children's understanding (Boaler, 2008;Lubienski,2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This growth in knowledge of children's mathematical thinking supported the participating teachers to develop more inclusive pedagogical approaches to mathematics teaching. The important relationship between learning in meaningful contexts and the development of more equitable classrooms is consistent with international policies and practices promoting inclusive education (Thomas, 2013;Slee, 2013;Allan, 2010;Armstrong, Armstrong & Spandagou, 2010). Similarly in elementary mathematics classrooms in which lessons are structured to include all children purposefully, there are clear connections between teaching content, teachers' pedagogical knowledge and knowledge of children's understanding (Boaler, 2008;Lubienski,2000).…”
Section: Discussionmentioning
confidence: 99%
“…A more radical view of inclusion recognises inclusive education as the restructuring of schools so that they become places for all children (Slee, 2011;Allan, 2010). If we are to have schools for all children then we must have classrooms in which everyone is a member of a 'community of learners' (Thomas, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…He keeps saying that he did something about it, but nothing changes so then at some point I was just like forget it. (The Netherlands, pupil) Research has suggested that the views of disabled pupils are often overlooked in processes of transition (O'Donnell, 2003) and that processes of inclusion should be sympathetic to concerns of all the actors involved (Allan, 2010;Evans & Lunt, 2002;Farrell, 2001). Children in our project, in contrast to the "expert professional" perspective, believed that child-led settings improved academic performance and led to quicker change and that such a setting required professionals to be accepting of difference:…”
Section: Child-involved Child-led and Peer-supported Transitionmentioning
confidence: 98%
“…Such writing raises questions concerning how we can restructure culture, policy and practices so all involved in the education of children respond to the diversity of students' requirements. It also raises questions for this paper concerning whose views are given credence, who is enabled to adopt leadership positions, whether there is collaborative problem-solving and what concepts underpin decision-making during the process of inclusion and transition (Allan, 2010;Davis & Deponio, 2014;Davis et al, 2012;Kinsella & Senior, 2008;O'Donnell, 2003).…”
Section: Messages From the Literaturementioning
confidence: 98%
“…In a school system where measurement, ranking and competition have a prominent place, the school's wider aims and ambitions are difficult to enforce. Allan (2010) writes about the problems that the quest for inclusion in Europe has faced since 2000. She notes that large-scale and optimistic inclusion projects in countries such as Germany, Holland and Austria have been less successful and argues Schools have been given additional resources, in the hope that they will develop 'good practice' that can be transferred to other schools.…”
Section: From Integration To Inclusionmentioning
confidence: 99%